(untitled) (Research, Society and Development, 2021)
Objective: The aim of this study is to carry out a literature review about the impacts caused by endodontic treatment by conservative endodontic cavities compared to traditional endodontic cavities. Methodology: A bibliographic search on the topic was carried out in the Pubmed and Scielo database, collecting articles between 2014 and 2020. Results: In incisor teeth with conservative endodontic cavities there is no increase in resistance compared to traditional cavities, but there is still no consensus in the literature regarding posterior teeth. Oval canals of teeth with conservative endodontic cavities showed more non-instrumented areas. Reports of apical transportation, change in the curvature canals, residual debris in the pulp chamber, difficulty in locating canals and increased treatment time in teeth with conservative cavities were also observed. Final Considerations: There is no evidence of increased fracture resistance in incisor teeth with conservative cavities and there is no consensus regarding posterior teeth. Because of this and the fact that this type of cavity brings some limitations to endodontic treatment, there is no reason to recommend it to the detriment of the traditional cavity, mainly without the use of magnification and ultrasound.